The INFLUENCE OF WEBSITE CAPABILITY, SERVICE PERFORMANCE, AND E-WOM ON STUDENTS PURCHASE DECISIONS ON MARKETPLACE IN PONTIANAK CITY - Khurnadi, Vicky; Graceallah, Georgerius (Journal of Business Studies and Management Review, 2025)
This study aims to examine the relationship between the variables of website capability, service performance, and electronic word of mouth (E-Wom) on students’ purchase decisions on the marketplace in Pontianak City, this study uses a quantitative approach with three independent variables, namely website capability, service performance, and e-Wom, as well as one independent variable, namely purchase decision. The population in the study is marketplace users in Pontianak City, with a sample of 124 students determined through nonprobability sampling with accidental sampling techniques and collected through questionnaires. The results of the study show that: (1) website capabilities have a positive and significant effect on purchasing decisions, which confirms that reliable and effective website quality is able to influence students’ purchasing decisions; (2) Service performance has a positive and significant effect on purchase decisions, so that service according to consumer expectations is able to increase purchases; and (3) e-WOM has a positive and significant influence on purchasing decisions, which means that a good review can influence a person to buy an item. These findings confirm the importance of website capabilities, service performance, and e-WOM as a way to improve purchasing decisions.